Monoclonal Antibodies to Intracellular Stages of Cryptosporidium parvum Define Life Cycle Progression In Vitro - Georgia Wilke (American Society for Microbiology, 2018)
ABSTRACT Among the obstacles hindering Cryptosporidium research is the lack of an in vitro culture system that supports complete life development and propagation. This major barrier has led to a shortage of widely available anti-Cryptosporidium antibodies and a lack of markers for staging developmental progression. Previously developed antibodies against Cryptosporidium were raised against extracellular stages or recombinant proteins, leading to antibodies with limited reactivity across the parasite life cycle. Here we sought to create antibodies that recognize novel epitopes that could be used to define intracellular development. We identified a mouse epithelial cell line that supported C. parvum growth, enabling immunization of mice with infected cells to create a bank of monoclonal antibodies (MAbs) against intracellular parasite stages while avoiding the development of host-specific antibodies. From this bank, we identified 12 antibodies with a range of reactivities across the parasite life cycle. Importantly, we identified specific MAbs that can distinguish different life cycle stages, such as trophozoites, merozoites, type I versus II meronts, and macrogamonts. These MAbs provide valuable tools for the Cryptosporidium research community and will facilitate future investigation into parasite biology. IMPORTANCE Cryptosporidium is a protozoan parasite that causes gastrointestinal disease in humans and animals. Currently, there is a limited array of antibodies available against the parasite, which hinders imaging studies and makes it difficult to visualize the parasite life cycle in different culture systems. In order to alleviate this reagent gap, we created a library of novel antibodies against the intracellular life cycle stages of Cryptosporidium. We identified antibodies that recognize specific life cycle stages in distinctive ways, enabling unambiguous description of the parasite life cycle. These MAbs will aid future investigation into Cryptosporidium biology and help illuminate growth differences between various culture platforms.